Pendidikan, Pengetahuan Dan Penggunaan Alat Pelindung Diri Pekerja PT. Martadinata Indah Tambang Kabupaten Donggala - Christine Christine; Djunaedil Syukur Sulaeman (Sanitasi: Jurnal Kesehatan Lingkungan, 2022)
Occupational safety and health contain the value of protecting workers from accidents or occupational diseases. Personal protective equipment is important to protect workers from injuries or illnesses caused by exposure to hazards in the workplace. PT. Martadinata Indah Tambang is a company that produces stone, gravel, crushed stone, and sand, located in Alindau Village, Sindue Tobata District, Donggala Regency with 89 workers and most of them have primary school education (48%). The work fields consist of sand production, gravel production, drivers, stone breaking, welding, heavy equipment, electricity, mechanics, checkers, drivers, logistics, and security. Workers in the production department were at risk of work accidents as they interacted directly with equipment and materials and were exposed to a work environment that had the potential to pose the risk of accidents and occupational diseases. This study aimed to analyze the relationship between education and knowledge with the use of personal protective equipment (PPE). This was an observational study with a cross-sectional design. The population size is 89 workers, and 47 workers as sampled by accidental sampling. As the results, using Chi-square for the statistical test, there was a significant relationship between the level of education and the use of personal protective equipment (p-value = 0,015), and also there was a significant relationship between knowledge and the use of personal protective equipment (p-value=0,003). The company should control the risk of hazards to avoid possible occupational diseases and work accidents.